INTENSITAS RESEARCH AND DEVELOPMENT, GOODWILL, INTELLECTUAL CAPITAL DAN PERFORMA FINANSIAL SEBAGAI PENENTU NILAI PERUSAHAAN - Ellen Monata Wahono; Shinta Permata Sari (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
The increasingly fierce competition that occurs between companies in the  current  era of globalization is forcing the company to improve its strategies. Therefore, the main purpose of establishing a company is to increase the value of the firm. To achieve that purpose,managers have to understand the factors that can increase the value of the firms and also fulfillthe interests of stakeholders. This study aims to analyze the effect of Research and Development Intensity (RnD), Goodwill (GDW), Intellectual Capital (IC), and Financial Performance (PF) on Firm Value. The research data is obtained from  the  annual reports  of  manufacturing  companies  listed  on the Indonesia  Stock  Exchange  in 2015-2019 with a total sample of 60 after meeting certain criteria. The data is analyzed using multiple linear regression analysis.The results show that goodwill, intellectual  capital,  and financial performance have an effect on firm value. Meanwhile, the intensity of research and development has no effect on firm value The increasingly fierce competition that occurs between companies in the  current  era of globalization is forcing the company to improve its strategies. Therefore, the main purpose of establishing a company is to increase the value of the firm. To achieve that purpose,managers have to understand the factors that can increase the value of the firms and also fulfillthe interests of stakeholders. This study aims to analyze the effect of Research and Development Intensity (RnD), Goodwill (GDW), Intellectual Capital (IC), and Financial Performance (PF) on Firm Value. The research data is obtained from  the  annual reports  of  manufacturing  companies  listed  on the Indonesia  Stock  Exchange  in 2015-2019 with a total sample of 60 after meeting certain criteria. The data is analyzed using multiple linear regression analysis.The results show that goodwill, intellectual  capital,  and financial performance have an effect on firm value. Meanwhile, the intensity of research and development has no effect on firm value